Pressure fluctuation in high-Reynolds-number turbulent boundary layer: Results from experiments and DNS - Tsuji, Yoshiyuki; Imayama, Shintaro; Schlatter, Philipp; Alfredsson, P. Henrik; Johansson, Arne V.; Marusic, Ivan; Hutchins, Nicholas; Monty, Jason (Journal of Turbulence, 2012)
We have developed a small pressure probe and measured both static pressure and wall pressure simultaneously in turbulent boundary layers up to Reynolds numbers based on the momentum thickness Rθ ≃ 44,620. The measurements were performed at large experimental facilities in Sweden, Australia, and Japan.We find that the measured pressure data are contaminated by the artificial background noise induced by test section and are also affected by the flow boundary conditions. By analyzing data from different wind tunnels acquired at the same Reynolds number, we evaluate the effect of background noises and boundary conditions on the pressure statistics. We also compare the experimental results with results of direct numerical simulations and discuss differences in boundary conditions between real and simulated wind tunnels. © 2012 Taylor & Francis.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Background noise; Direct numerical simulation; Flow boundary conditions; Outer and inner scaling; Static-pressure fluctuation; Turbulent boundary layer; Wall pressure